Explorando los métodos de planeación en las organizaciones (2016)
This article is complementary to the letter “A theoretical approach to planning in organizations”, originated within the framework of the research project on the behavior of entrepreneurs against integration agreements. Its aim is to explore the most common methods in planning organizations, in order to identify the processes that are adopted in the decision making. Methodologically, the work was developed through a literature review on the subject. The results show that there are several methods that each organization can adapt according to your environment and context.